Novel and Emerging Strategies for Longitudinal Data Collection. Issue 2 (9th December 2014) - Udtha, Malini; Nomie, Krystle; Yu, Erica; Sanner, Jennifer
Abstract Purpose To describe novel and emerging strategies practiced globally in research to improve longitudinal data collection. Organizing Construct In research studies, numerous strategies such as telephone interviews, postal mailing, online questionnaires, and electronic mail are traditionally utilized in longitudinal data collection. However, due to technological advances, novel and emerging strategies have been applied to longitudinal data collection, such as two‐way short message service, smartphone applications (or "apps"), retrieval capabilities applied to the electronic medical record, and an adapted cloud interface. In this review, traditional longitudinal data collection strategies are briefly described, emerging and novel strategies are detailed and explored, and information regarding the impact of novel methods on participant response rates, the timeliness of participant responses, and cost is provided. We further discuss how these novel and emerging strategies affect longitudinal data collection and advance research, specifically nursing research. Conclusions Evidence suggests that the novel and emerging longitudinal data collection strategies discussed in this review are valuable approaches to consider. These strategies facilitate collecting longitudinal research data to better understand a variety of health‐related conditions. Future studies, including nursing research, should consider using novel and emerging strategies to advance longitudinal data collection. Clinical Relevance A better understanding of novel and emerging longitudinal data collection strategies will ultimately improve longitudinal data collection as well as foster research efforts. Nurse researchers, along with all researchers, must be aware of and consider implementing novel and emerging strategies to ensure future healthcare research success.